1977
DOI: 10.1037/h0081426
|View full text |Cite
|
Sign up to set email alerts
|

The psychological effects of hysterectomy.

Abstract: Although hysterectomy remains one of the most common forms of surgery to which women are likely to be exposed the psychological implications remain obscure. Psychological factors have been investigated both as independent and dependent variables but a variety of procedural and design shortcomings leave importance of such factors obscure. The more common faults include an undue emphasis on retrospective designs, inadequate controls, contamination of assessment procedures and failure to quantify and adequately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Studies have found psychological morbidity such as anxiety and depression to be associated with hysterectomy [16,17]. Flory et al [9] reported that hysterectomy had negative short-and long-term psychological consequences for some women.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found psychological morbidity such as anxiety and depression to be associated with hysterectomy [16,17]. Flory et al [9] reported that hysterectomy had negative short-and long-term psychological consequences for some women.…”
Section: Discussionmentioning
confidence: 99%
“…1 In a 1977 review of 21 studies of women who underwent hysterectomy, 15 studies showed undesirable psychological reactions to hysterectomy, whereas 6 showed no effect. 2 These early studies led to the notion that hysterectomy might result in increased psychological morbidity and psychiatric problems. These studies, however, had a number of methodological limitations.…”
mentioning
confidence: 99%
“…Hysterectomy has a low mortality (Centerwall 1981;Richards 1978) and little short-term morbidity, but there is controversy over the longterm effects, both psychiatric and physical. Some studies indicate beneficial psychiatric effects (Richards 1978;Coppen et al 1981;Bragg 1965;Meikle 1977) others state that hysterectomy is frequently followed by depression requiring treatment (Richards 1973(Richards , 1974Melody 1962;Barglow et al 1965;Barker 1968;Hollender 1960;Meikle 1977).…”
mentioning
confidence: 99%